Pengaruh Model PBL Terhadap Hasil Belajar Materi Membuat Keputusan Kelas II SDN KAG 02 - Putri, Dwi Ariyanti; Prayito, Muhammad (DIKDAS MATAPPA: Jurnal Ilmu Pendidikan Dasar, 2024)
This research is based on low student learning outcomes and activities that are not in favor of students. The aim of this research is to see the influence of the PBL model on student learning outcomes in the material Making Decisions in class II of SD N Karanganyar Gunung 02 Semarang. This type of research is quantitative with a One-Group-Pretest-Posttest design. The sample used was class II B students at SD N Karanganyar Gunung 02 Semarang, totaling 30 students with 14 students and 16 female students. The research results obtained show that there is an increase in the value of learning. The average pretest score is 57.83 and the posttest score is 88.50. Apart from that, the PBL model also has an influence in improving student learning outcomes as shown in the average NGain value of 0.7339, where it is stated that the PBL model has a high influence. Based on the results of the research conducted, it can be concluded that the application of the PBL model in learning is able to improve student learning outcomes in the material for Making Decisions in Civics subjects. Apart from that, varied learning activities can also create meaningful experiences for students.